Representasi Pelanggaran Kode Etik Jurnalistik pada Serial Drama Korea HUSH - Rosyidah, Thalia Fikriatur; Hakim, Lukman (Tuturlogi: Journal of Southeast Asian Communication, 2023)
The journalistic code of ethics, which is the heart of journalistic products and is a beacon in the world of journalism, is in fact still very vulnerable to being violated. This research aims to determine forms of violation of the journalistic code of ethics, not only based on the Indonesian journalistic code of ethics, but also using the journalistic code of ethics of South Korea, the country where this drama series originates. This research was conducted on the Korean drama series HUSH which aired in 2019 with 16 episodes. The author uses the Indonesian Press Council's journalistic code of ethics and the South Korean Press Code of Ethics to analyze the violations. Apart from that, the causes and consequences of violations of the journalistic code of ethics that occur can also be found. This research uses a qualitative descriptive method with the Pierce model of semiotic approach. The research results showed that: (1) there were 5 cases that showed violations of the journalistic code of ethics. (2) the cause of the violation of the journalistic code of ethics was discovered, namely the existence of a special relationship between the high-ranking officials involved in the case and the leader of the Korean Daily, as well as considering that accepting bribes by people who work in the field of journalism is considered a normal thing.